Comet assay technique for indicator of DNA damage in Turkish Awassi sheep - Azzawi, M. S.; AL-Ani, A. A.; AL-Anbari, N. N. (Journal of Kerbala for Agricultural Sciences, 2016)
This study was carried out at the Ruminants Researches Station (20 km west of Baghdad) /State Board for Agriculture Researches / Ministry of Agriculture, Reproductive laboratory in college of Agriculture/Univ. of Baghdad & Technical Center of AL-Nahrain Univ. over period from 1/1/213 until 1/6/2014. The aim of this study was to find DNA damage according to comet assay procedure, after a test of sheep for incidence of blood parasites. Significant effect (P≤0.05) of incidence of blood parasites on daily milk yield , total milk production, protein and total solid non-fat percentage were recorded, but no-significant effect of incidence on other parameters of milk. The present study,for more accuracy,suggest to applied on larger sample of sheep.